The schoolwide enrichment model a how-to guide for talent development - Renzulli, Joseph S. 1936-; Reis, Sally M. (Prufrock Press, 2014)
The Schoolwide Enrichment Model: A How-to Guide for Educational Excellence (3rd ed.) presents an inspirational model for helping students achieve in today''s schools. Based on years of research, the Schoolwide Enrichment Model (SEM) is founded on highly successful practices developed for programs for gifted students and promotes ""a rising tide lifts all ships"" approach to school improvement. This guidebook shows educators step-by-step how to develop their own SEM program based on their own local resources, student population, and faculty. Instead of treating students as simply test numbers i
Description based upon print version of record
Keywords: Gifted children -- Education -- United States; Gifted children -- Education -- Curricula -- United States; Curriculum enrichment; Electronic books